Jordbruk och mjölkproduktion med kor i Etiopien - Allard, Helena (2008)
Ethiopia is the country with most livestock per capita on the continent of Africa. There are 34.5 million cattle that are used for drought, meat- and milkproduction and 85% of the population rely on agriculture for their survival in some way. Milk is produced in four main systems, through pastoralism in the lowlands, in mixed crop-livestock systems in the highlands, in and near big cities with only one or two cows, and in intensive farming systems. There are 17 cattle breeds in Ethiopia and some of them are more suitable for milk production than others. Several environmental and economic problems arise from livestock holding in the country, for example overgrazing, low production due to feed shortage, low quality of the avaible feed and non-existing breeding programs. Drought and failure to collect water during the rainy season are contributing even more to these problems. Some solutions could be to improve production through breeding programs and more nutrious feed. Feed could be more widely conserved during the rainy season and the water could also be collected during this time. Drought-resistant crops should replace some of the water demanding plants that are cultivated today. Crosses between African and foreign high producing cows have showed to be sucessfull and could be wider used among livestock holders.